If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2x + 2) = -1(-3x + 5) + -1x Reorder the terms: 5 + -1(2 + 2x) = -1(-3x + 5) + -1x 5 + (2 * -1 + 2x * -1) = -1(-3x + 5) + -1x 5 + (-2 + -2x) = -1(-3x + 5) + -1x Combine like terms: 5 + -2 = 3 3 + -2x = -1(-3x + 5) + -1x Reorder the terms: 3 + -2x = -1(5 + -3x) + -1x 3 + -2x = (5 * -1 + -3x * -1) + -1x 3 + -2x = (-5 + 3x) + -1x Combine like terms: 3x + -1x = 2x 3 + -2x = -5 + 2x Solving 3 + -2x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + -2x + -2x = -5 + 2x + -2x Combine like terms: -2x + -2x = -4x 3 + -4x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + -4x = -5 + 0 3 + -4x = -5 Add '-3' to each side of the equation. 3 + -3 + -4x = -5 + -3 Combine like terms: 3 + -3 = 0 0 + -4x = -5 + -3 -4x = -5 + -3 Combine like terms: -5 + -3 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 3(-2x+5)=9 | | 1x+.5y=6 | | 21=7y+7+(y+3) | | 7(-6x+1)=-329 | | X-2(x+3)=-2(x+1)-4 | | 2x+1+3x=30 | | x=a(a-b)+b(a+b) | | x=-3+13 | | 2x-3+19=17 | | 5x=63.25 | | [2x+3]=-5 | | 7(-1x+5)=-7 | | x^2-2+3x+8=180 | | -8y=48-4y | | 7.1x+4.4-2x-8.7= | | -7(2x+4)=-70 | | [8x+5]=21 | | 72-10x=12 | | -6x+2=3x-79 | | [4x-8]=20 | | x+4=-20-x | | 6x-3=-7x-133 | | 4-3x+2x=-18+2 | | 6=16-13d | | -140=4x-6(-x+10) | | 5y=-2x-15 | | 10x^2-42x+44=0 | | 5x+13=35+7x | | -1-2x-6x=-65 | | 5x-4=30x+16 | | 6x-4(2-x)=14 | | -17=-2x-2x-5 |